The Co-Occurrence of Conduct Problems and Depressive Symptoms From Childhood to Adulthood for Men: Stability Over Time and Prediction to Substance Use - Deborah M Capaldi; Stacey S Tiberio; David CR Kerr; Lee D Owen (SAGE Publishing, 2023)
The dual pathway hypothesis of risk for substance use was tested by examining risk from symptoms of conduct problems and depressive symptoms in adolescence (from ages 10-11 to 17-18 years) to substance use-including tobacco, alcohol, cannabis, and other illicit drugs-in both early adulthood (approximately from ages 20 to 29 years) and middle adulthood (approximately from ages 29 to 38 years). Hypotheses were tested on a sample of boys who were at risk for conduct problems by virtue of the neighborhoods where they lived in childhood (the Oregon Youth Study; N = 206 at Wave 1). Dual-trajectory modeling (Latent Class Analysis) resulted in a 3-group solution of high, moderate, and low co-occurring symptoms. The latent class of boys with co-occurring symptoms in adolescence showed higher levels of substance use in adulthood; namely, higher levels of cannabis and illicit substance use during early adulthood compared to either of the moderate or low symptom classes, and higher use of cannabis in midadulthood than the low symptom class. Those with co-occurring symptoms also showed, overall, higher vulnerability to use of tobacco in these 2 periods, but not to higher use of alcohol. Regression analyses indicated that the higher substance use of the co-occur group of men was related to their adolescent conduct problems, but was not related to their adolescent depressive symptoms; however, these associations were nonsignificant when adolescent use of the respective substances were included in the models. Thus, the dual-trajectory hypothesis was not supported. However, the findings indicated that, as assessed in the present study, the psychopathology symptoms of boys with conduct problems in adolescence who show risk for later substance use may be complex, involving depressive symptoms.